(untitled) (UNWE Yearbook, 2008)
Entrepreneurial attitudes such as "willingness to change" and "taking risks" in a nowadays widened European context may be considered crucial prerequisites of success, especially under conditions in times of dynamic change as, e.g., enlargement of markets in the process of EU integration with resulting challenges for necessary adjustments and strategic responses. The question, thus, arises which in such an environment might be the more adaptive or appropriate entrepreneurial "type"?Questioning, thereby, perhaps more pointedly: Do entrepreneurs - and if so, how (?) - react, when confronted with such challenges? Do they react at all, and if so again, are there any discernible behavioral patterns of pro-active response and strategic adjustment?